Three-dimensional sonoangiography in the uterine cervix assessment in postmenopausal women - Czekierdowski, Artur; Kotarski, Jan; Daniłoś, Jarosław; Stachowicz, Norbert (Menopause Review/Przegląd Menopauzalny, 2003)
Objectives: The aim of our paper was to study the usefulness of new three-dimensional blood flow indices in the vascularity assessment of cervical cancer in postmenopausal women. Material and methods: We have assessed 38 women with 3D transvaginal probe and automatic volume measurement (VOCAL) using Voluson V730 scanner (Kretztechnik, Austria). Uterine artery blood flow and uterine cervix vascularity indices (vascular index, VI, flow index FI and vascularity-flow index VFI) were measured in all women. All ultrasound measurements were verified by histology. Study group included women with cervical carcinoma, women with cervical intraepithelial neoplasia CIN 1-2 and women with no histological changes found in D&C or hysterectomy specimens. Results: Mean age of the studied group was 54.3±6.2 years (range 49–78 years). There were no differences in HRT use, BMI values and years after menopause in the studied subgroups of patients which included 15 women with normal cervix, 11 had CIN 1–2 lesions and 12 had cervical cancer, FIGO stage Ib–IIa. 3D power Doppler sonography revealed that chaotic blood vessel arrangement and tortuous blood vessel network was characteristic for women with cervical cancer in most cases. There were significant differences in means of cervical blood flow and vascularity indices between women with cervical cancer and two other study subgroups (both p<0.005). In contrast, there were no significant differences in mean values of Doppler blood flow indices measured in uterine artery. Conclusion: We conclude that uterine cervix should be assessed during transvaginal sonography. Three-dimensional sonography with 3D blood flow indices measurements might be used to better characterize cervical cancer vascularity in postmenopausal women.